Evaluating Effects of Building Envelope Thermal Loads on Energy use and Thermal Comfort for a Bedroom TAC System. (May 2017) - Ning, Mao; Mengjie, Song; Dongmei, Pan; Shiming, Deng
Abstract: There has been an increasing concern on thermal comfort in sleeping environments and its associated energy use in the past few years. To improve the thermal environment and reduce energy use of air conditioning in bedrooms, task/ambient air conditioning (TAC) can be applied and was studied previously. Due to the variation of the envelope thermal loads in a bedroom during night, it is necessary to study the thermal environment inside the bedroom and the energy use of a TAC system for the bedroom at varying envelope thermal loads. Therefore, this paper reports on a numerical study on a TAC system applied to a bedroom with different envelope heat gains. PMV and EUC (energy utilization coefficient) values were evaluated, respectively. The study results indicated that when envelope thermal loads was higher, the advantage of the TAC system in energy saving was greater for the same thermal comfort level. However, it should be noted that a higher envelope thermal load could also resulted in the non-uniformity in air flow and air temperature distributions, leading to a possible uncomfortable micro environment.